Efisiensi Penerapan Fintech dan Digitalisasi dalam Memaksimalkan Market Share Perbankan Syariah Pada Masa Pandemi Covid 19 - Indah Lestari Ritonga; Ahmad Amin Dalimunte (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2022)
The purpose of this study is to try to provide an overview of the efficiency of implementing fintech and digitalization that must be done by Islamic banking, one of which is at Bank Sumut Medan Sharia Branch Office. The method used in this study is a descriptive qualitative method. Data collection techniques by conducting a literature study approach (library research) and interviews. The results showed that the state of implementation and cooperation with fintech companies has not been running as has been done by conventional Sumut Banks. However, in the future Bank Sumut Syariah will realize the release or add some banking services with a digitalization system. With the hope of implementing fintech and the realization of more optimal digitization services at PT Bank Sumut, Medan Sharia Branch Office is expected to be able to provide progress and maximize market share in Islamic banking